2022
DOI: 10.18535/ijsrm/v10i5.el01
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Student Teaching Interns’ Journey in an Online Mode of Teaching Delivery

Abstract: The COVID – 19 pandemic resulted in significant educational reforms. Even the once-in-a-lifetime face-to-face student teaching experience has been transformed into a virtual reality. The havoc caused by today's difficulties prompted the creation of this article, which looked at the journey of student teaching interns as they completed online teaching demonstrations and other tasks as part of their student internship. Three sub-themes arose using Charmaz's (2006) constructivist grounded theory: introspection as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Using the STI module allows the teaching interns to evaluate themselves as they reported that the activities helped them to explore their strengths and weaknesses. Their experiences in virtual teaching internship support the theory regarding the phases of melting among teaching interns when using the online instructional delivery mode (Quinco-Cadosales, 2022). According to this theory, the teaching interns engage in introspection by being aware of their feelings, expectations, and anxieties.…”
Section: Exploring One's Selfmentioning
confidence: 71%
“…Using the STI module allows the teaching interns to evaluate themselves as they reported that the activities helped them to explore their strengths and weaknesses. Their experiences in virtual teaching internship support the theory regarding the phases of melting among teaching interns when using the online instructional delivery mode (Quinco-Cadosales, 2022). According to this theory, the teaching interns engage in introspection by being aware of their feelings, expectations, and anxieties.…”
Section: Exploring One's Selfmentioning
confidence: 71%
“…Commitment to one's profession is one of the things that drives teachers to continue doing their duties as teachers. In the face of shifting needs and interests, commitments make people's conduct predictable, making it easier to plan and coordinate group actions involving several agents (Michael & Pacherie, 2015;Quinco-Cadosales, 2018). Additionally, commitment encourages cooperation by causing people to be willing to participate in joint efforts that they otherwise would not be if they and others were not committed to doing so (Michael et al, 2016).…”
Section: Commitmentmentioning
confidence: 99%